Nemzetiszocialista jogátadás magyar szemszögből : A jogátadás okai, formái és hatása a magánjog területén - Herger, Eszter Cs. (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2025)
The academic relations between Hungarian and German law scholars between 1920 and 1944 (especially since 1933) have not yet been comprehensively analysed by either German or Hungarian legal historians. This article focuses on the reactions of Hungarian private law scholars to the National Socialist intention to transfer law, be it enthusiastic, reserved, rejecting or even silently accepting, as well as the presentation of the development of contemporary jurisprudence on the basis of archival sources, especially in the areas of family, inheritance, commercial and civil procedural law. The question of the extent to which German legal influence played a role in shaping theory and practice in Hungary and where – despite the similarities – nationally specific legal solutions can be found is investigated.